2012
DOI: 10.1186/2193-1801-1-21
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for conservation and sustainable use in a fragment of the Atlantic forest in southeastern Brazil by a traditional human group

Abstract: The use of forest resources by a rural community adjacent to a Biological Reserve was examined using quantitative methods based on the consensus of six local specialists. Plants with trunk diameters at 1.3 m above soil level (DBH) ≥ 5 cm were sampled in 0.5 ha of forest and their use-value (UV) were calculated and associated with their structural descriptors. A total of 129 species were identified, and 69 of them having known uses. The species with largest UV were: Xylopia sericea, Lecythis lanceolata and Guar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
3
5
0
Order By: Relevance
“…Saiter et al (2011) reports a very high species richness of Myrtaceae in the dense ombrophilous forests of the Espírito Santo mountains (83 species from a total of 399 species in 1.02 hectares). This would agree in theory with the findings of Christo et al (2012) of a significant and positive association between the use-value of a given family and its number of species in the surrounding environment.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Saiter et al (2011) reports a very high species richness of Myrtaceae in the dense ombrophilous forests of the Espírito Santo mountains (83 species from a total of 399 species in 1.02 hectares). This would agree in theory with the findings of Christo et al (2012) of a significant and positive association between the use-value of a given family and its number of species in the surrounding environment.…”
Section: Discussionsupporting
confidence: 91%
“…With the exclusion of herbaceous plants, our study stresses the importance of native trees as sources of food, supporting the findings of Fonseca- Kruel and Peixoto (2004). While other studies show a high number of species being commonly employed for construction and technology (Cruz da Cunha and Albuquerque 2006, Borges and Peixoto 2009, Christo et al 2012, this often deleterious form of management was not observed to be frequent for our population. The management practices for native species that we encountered are fairly homogeneous and non-destructive, represented in great part by the collection of edible fruits.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A mistake in the table legend of the study by Christo et al. () was corrected because the data were presented as absolute density when they actually should have been presented as the absolute frequency and vice versa. The error was corrected after reviewing another study by these authors conducted in the same area (Christo et al.…”
Section: Methodsmentioning
confidence: 99%
“…Important policies were implemented in the last decade to encourage research and development related to the use of medicinal plants and herbal remedies which may be provided with quality, safety and efficacy to the population, prioritizing the country's biodiversity [14]. Considering the actual worldwide popular use of medicinal plants, the Sistema Único de Saúde (SUS, Brazilian Health System), via the Brazilian Ministry of Health, has introduced the National Policy on Integrative and Complementary Practices and the National Policy on Medicinal Plants in 2006 [13,15] medicinal plants via physicians of SUS has not only raised their consume in health care but has also helped to educate about possible dangers of their indiscriminate use. As prescription of local herbal medicines by qualified professionals and accurate information have increased and this will help to prevent medical application of unsafe and ineffective plants [16,17].…”
Section: Introductionmentioning
confidence: 99%